Affectedness, empowerment and norm contestation – children and young people as social agents in international politics - Anna Holzscheiter (Third World Thematics: A TWQ Journal, 2018)
In my contribution to this collection, I aim to expose how the growing transnationalisation of groups of affected persons – in this case children and young people – has brought to the fore normative contradictions and tensions built into the 1989 UN Convention on the Rights of the Child. More specifically, I will show how the universal notion of children's rights and a strong global consensus on the `scourge' of child labour has been challenged through the empowerment of affected persons – in this case child workers. Building on critical constructivist thinking on norms, my core argument is that the increasing access of affected persons' organisations (APOs) to international organisations and high-level events brings with it an increase in norm contestation. Rather than creating new normative contestations, I will show in my analysis, the inclusion of the most affected brings to light normative inconsistencies and ambiguities that have been potentially ingrained in international treaties but hitherto successfully suppressed by powerful norm advocates. The articulation of subversive perspectives on child labour by working children and young people, I will conclude, results in normative tensions and collisions and a reconsideration of seemingly universal values previously taken for granted.
Keywords: 330; children and youth; civil society; participation and power; labour; governance